Open irreversible electroporation for isolated local recurrence of pancreatic ductal adenocarcinoma after primary surgery - Heger, Ulrike; Mack, Claudia; Tjaden, Christin; Pan, Feng; Pausch, Thomas; Hinz, Ulf; Sommer, Christof-Matthias; Hackert, Thilo (Pancreatology, 2021)
Background/objectives - Irreversible electroporation (IRE) is an emerging treatment for locally advanced pancreatic cancer (LAPC) which in some cohorts has been associated with severe complications. Additionally, re-resection of isolated local recurrence (ILR) after pancreatic ductal adenocarcinoma (PDAC) can improve survival. We investigated safety, feasibility and oncologic outcomes in the first report on open IRE for unresectable ILR of PDAC in a staged surgical approach. - Methods - Records of the prospectively documented institutional database were screened for patients undergoing laparotomy in IRE-standby due to questionable resectability. Endpoints were morbidity, mortality and overall (OS) and progression free survival (PFS). Data of LAPC and ILR were compared statistically for safety and feasibility analysis. - Results - Intraoperative IRE was performed in 11 ILR and 14 LAPC. Six (54.5%) ILR and 10 (71.4%) LAPC patients had postoperative complications, type and frequency did not differ significantly. Major complications occurred in one ILR and two LAPC patients. Median OS was 20.0 months (95% CI: 2.7-37.3) after IRE for ILR and 28 (17.4-38.6) for LAPC. Median PFS after IRE was seven months for both ILR (4.1-9.9; n = 9) and LAPC (2.3-11.7; n = 13). - Conclusion - Open IRE for unresectable ILR was associated with acceptable perioperative risk. In this small, highly selected subset of patients with limited therapeutic options ancillary treatment with IRE might improve survival. Randomized treatment studies are required to establish the definitive role of IRE as compared to palliative standards of care in unresectable recurrence of PDAC and inconvertible LAPC.
Gesehen am 12.04.2022